The Statement of Comprehensive Income – A New Disclosure Concept - Marzena REMLEIN; Małgorzata RÓWIŃSKA-KRÁĽ (Communications of International Proceedings, 2020)
The goal of the paper is to critically assess the current solutions in the field of disclosure of components of comprehensive income in financial statements and to develop a proposal for the structure of the statement of comprehensive income that will improve its usefulness. Based on the literature studies and the results of previous empirical research on comprehensive income reporting, the authors of the paper formulated the following thesis: The principles of disclosing comprehensive income in accordance with the law do not provide optimal information about the financial effects of the entity's operations. The paper is structured as follows. Section 1 presents the outline the concepts of comprehensive income reporting. In Section 2 we describe our idea of disclosure of comprehensive income. Section 3 includes our empirical research and application of a new concept of the statement of comprehensive income in practice. The last section contains final comments on the use of the new concept of the statement of CI in assessing the company's profitability. Our proposal will contribute to the increased transparency of the statement of comprehensive  income and will help the users of financial statements in proper understanding of the significance of comprehensive income and other comprehensive income. The proposed structure of the statement of comprehensive income is also intended to assist users in interpreting the ratios calculated on its basis.
Keywords: Comprehensive Income; Net Income